A Clean-Label Formulation of Fortified Yogurt Based on Rhododendron Flower Powder as a Functional Ingredient - Alina Narcisa Postolache; Ionuț Dumitru Veleșcu; Florina Stoica; Ioana Cristina Crivei; Vlad Nicolae Arsenoaia; Marius Giorgi Usturoi; Cristina Gabriela Constantinescu (Pop); Florin Daniel Lipșa; Gabriela Frunză; Daniel Simeanu; Roxana Nicoleta Rațu (Foods, 2023)
The world-wide-dispersed Rhododendron is a tiny, evergreen plant with vivid red or pale pink blossoms that is a member of the Ericaceae family and is well-known for its stunning flowers. To improve yogurt’s nutritional profile and sensory qualities, this study investigates an innovative application of Rhododendron flower powder (RFP). The potential health benefits of Rhododendron flowers, which are a rich source of bioactive compounds such as polyphenols and antioxidants, have attracted attention. Consequently, the physicochemical, phytochemical, and sensory qualities of fortifying yogurt with RFP at various concentrations were studied. The results showed that the texture and color of the yogurt were highly influenced by the addition of RFP. The addition of this functional ingredient also resulted in a significant increase in the yogurt’s polyphenol content and antioxidant capacity. These findings demonstrate the suitability of RFP in yogurt formulations as a functional food ingredient, being a good source of phenolics.